Searches for H2O masers toward narrow-line Seyfert 1 galaxies. (4th May 2018) - Hagiwara, Yoshiaki; Doi, Akihiro; Hachisuka, Kazuya; Horiuchi, Shinji
Abstract: We present searches for 22 GHz H2 O masers toward 36 narrow-line Seyfert 1 galaxies (NLS1s), selected from known NLS1s with v sys ≲ 41000 km s −1 . Out of the 36 NLS1s in our sample, 11 have been first surveyed in our observations, while the observations of other NLS1s were previously reported in literature. In our survey, no new water maser source from NLS1s was detected at the 3σ rms level of 8.4 mJy to 144 mJy, which depends on different observing conditions or inhomogeneous sensitivities of each observation using three different telescopes. It is likely that the non-detection of new masers in our NLS1 sample is primarily due to insufficient sensitivities of our observations. Including the five known NLS1 masers, the total detection rate of the H2 O maser in NLS1s is not remarkably different from that of type 2 Seyfert galaxies or LINERs. However, more extensive and systematic searches of NLS1 would be required for a statistical discussion of the detection rate of the NLS1 maser, compared with that of type 2 Seyferts or LINERs.